The Development of Virtual Reality-Based Learning Media to Enhance University Students’ Motivation and Interest in Studying Non-Euclidean Geometry - Chintia Utami; Rizky Ananda; Amanda Nurhayati Siagian; Maigani Maigani; Fevi Rahmawati Suwanto (STKIP Singkawang, 2026)
This research aims to develop a Virtual Reality (VR)-based learning media using the Spatial.io platform to enhance the motivation and interest of mathematics education students in understanding Non-Euclidean Geometry. The study employed the Research and Development (R&D) method with the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. In the Analysis stage, the learning needs and the difficulties students face in grasping abstract concepts in geometry were identified. The media was then designed and developed using a virtual museum concept hosted on Spatial.io, featuring immersive rooms that visualized complex geometric structures. Expert validation was conducted involving media and material validators, with the results showing that the media was categorized as “very valid,” achieving an average score above 90% across all validation aspects. During the Implementation stage, the VR media was tested on mathematics students, and their affective responses were collected through Likert-scale questionnaires focusing on interest, motivation, practicality, and effectiveness. The evaluation results indicated that the VR-based media was highly practical (average score: 84%) and very effective (average score: 82.4%) in improving learning engagement. Moreover, the affective responses demonstrated a significant increase in both motivation and interest in learning abstract mathematical content. In conclusion, the development of Virtual Reality learning media for Non-Euclidean Geometry effectively supports the learning process by offering immersive, interactive, and contextually meaningful experiences that foster student involvement and emotional connection with the subject. Therefore, VR can be considered a highly relevant and impactful technological innovation to be integrated into mathematics learning at the higher education level.Pengembangan Media Pembelajaran Virtual Reality untuk Meningkatkan Motivasi dan Minat Belajar Mahasiswa pada Materi Geometri Non-EuclidABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis Virtual Reality (VR) menggunakan platform Spatial.io guna meningkatkan motivasi dan minat belajar mahasiswa pendidikan matematika terhadap materi Geometri Non-Euclid. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang terdiri dari lima tahap, yaitu: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Pada tahap analisis, diidentifikasi kebutuhan pembelajaran serta kesulitan mahasiswa dalam memahami konsep geometri yang bersifat abstrak. Media kemudian dirancang dan dikembangkan dalam bentuk museum virtual berbasis Spatial.io, yang memvisualisasikan bentuk-bentuk geometri non-konvensional secara imersif dan interaktif. Validasi media dilakukan oleh ahli materi dan ahli media, yang menunjukkan bahwa media yang dikembangkan termasuk dalam kategori “sangat valid” dengan rata-rata skor validasi di atas 90%. Pada tahap implementasi, media diuji coba pada mahasiswa jurusan matematika, dan data afektif dikumpulkan melalui angket skala Likert yang mencakup indikator minat, motivasi, kepraktisan, dan keefektifan. Hasil evaluasi menunjukkan bahwa media VR tergolong sangat praktis dengan skor rata-rata sebesar 84% dan sangat efektif dengan skor rata-rata 82,4% dalam meningkatkan keterlibatan belajar. Selain itu, respon afektif mahasiswa menunjukkan peningkatan yang signifikan dalam minat dan motivasi belajar terhadap konten matematika yang kompleks. Dengan demikian, media pembelajaran berbasis Virtual Reality ini terbukti mampu mendukung proses pembelajaran dengan menghadirkan pengalaman belajar yang imersif, interaktif, dan bermakna secara kontekstual. Oleh karena itu, media VR sangat relevan untuk diintegrasikan dalam pembelajaran matematika di jenjang pendidikan tinggi.Kata Kunci :Media Pembelajaran; Virtual Reality; Geometri Non-Euclid; Minat Belajar; Motivasi Belajar